A Case of Laparoscopic Resection Using the ICG Fluorescence for Peritoneal Disseminations of Hepatocellular Carcinoma - Kishimoto, Tomoya; Hashimoto, Yasuji; Mizuno, Manatsu; Nakano, Hiroya; Fukada, Akio; Nagano, Shinnosuke; Kidogami, Shinya; Mokutani, Yukako; Hirose, Hajime; Kawada, Junji; Yoshioka, Shinichi; Fujita, Junya; et al. (Gan to kagaku ryoho, 2022)
A 71-year-old male had repeated resection and transcatheter arterial chemo-embolization(TACE)for hepatocellular carcinoma(HCC). Treatment with lenvatinib was started due to multiple liver recurrences and peritoneal disseminations. Since only the disseminated lesion had increased, it was decided to perform laparoscopic resection. Indocyanine green(ICG) was intravenously injected the day before surgery. Disseminated lesions could be easily detected with intraoperative fluorescence imaging, and we could completely resect disseminated lesions. The ICG fluorescence could be considered to be useful in laparoscopic resection for peritoneal dissemination of HCC.